2009
DOI: 10.1523/jneurosci.2375-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Parkin Protects against LRRK2 G2019S Mutant-Induced Dopaminergic Neurodegeneration in Drosophila

Abstract: Mutations in the leucine-rich repeat kinase 2 (LRRK2) gene are currently recognized as the most common genetic cause of parkinsonism. Among the large number of LRRK2 mutations identified to date, the G2019S variant is the most common. In Asia, however, another LRRK2 variant, G2385R, appears to occur more frequently. To better understand the contribution of different LRRK2 variants toward disease pathogenesis, we generated transgenic Drosophila over-expressing various human LRRK2 alleles, including wild type, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
174
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(184 citation statements)
references
References 23 publications
(52 reference statements)
10
174
0
Order By: Relevance
“…Another recent study revealed that over-expression of LRRK2 accelerates the progression of neuropathological phenotypes in transgenic mice with the A53T α-synuclein mutation (85). In addition, Parkin alleviated dopaminergic neuronal loss mediated by over-expression of LRRK2 G2019S mutants (86). Combined together, these reports suggest functional linkages among the various FPD genes.…”
Section: Proteins Interacting With Lrrk2mentioning
confidence: 89%
“…Another recent study revealed that over-expression of LRRK2 accelerates the progression of neuropathological phenotypes in transgenic mice with the A53T α-synuclein mutation (85). In addition, Parkin alleviated dopaminergic neuronal loss mediated by over-expression of LRRK2 G2019S mutants (86). Combined together, these reports suggest functional linkages among the various FPD genes.…”
Section: Proteins Interacting With Lrrk2mentioning
confidence: 89%
“…Importantly, this effect was diminished by pharmacological inhibition of kinase activity of G2019S mutant or by overexpression of parkin, a protein implicated in autosomalrecessive Parkinsonism [116,117]. It was also suggested that DA neuron loss in Drosophila triggered by overexpression of G2019S hLRRK2 is caused by an increase in bulk protein synthesis and be prevented by overexpression of the phosphodeficient T136A ribosomal protein s15 [118].…”
Section: Direct Toxic Effects Of Lrrk2 Expression In Neuronsmentioning
confidence: 99%
“…In Drosophila, a dLRRK Y1383C mutant (analogous to human Y1699C) caused prominent vesicular aggregation of the protein and DA neuron loss [75]. Transgenic overexpression of human Y1699C or G2385R LRRK2 in Drosophila is also associated with DA neuron loss accompanied by locomotor deficits [117,122].…”
Section: Direct Toxic Effects Of Lrrk2 Expression In Neuronsmentioning
confidence: 99%
“…There have also been studies that relate LRRK2 and apoptosis (Ho et al, 2009). Previous studies have shown a relationship between LRRK2 and other PD-related proteins, such as parkin (Ng et al, 2009;, PINK-1 and DJ-1 (Venderova et al, 2009) or α-synuclein (X. Lin et al, 2009).…”
Section: Lrrk2 (Park8) and Paraquatmentioning
confidence: 99%